A CASE STUDY: ASSESSING THE CURRENT SITUATION OF FOREST PRODUCTS INDUSTRY IN TAŞKÖPRÜ THROUGH SWOT ANALYSIS AND ANALYTIC HIERARCHY PROCESS - Bayram, Bahadır Çağri; Üçüncü, Tutku (Kastamonu University, 2016)
The aim of the study is representing the situation of Taskopru's forest products industry and specify its optimum competitive strategy to make it more effective in the region. The condition of the industry in Taskopru was tried to be identified with a hybrid method which is composed of SWOT analysis and analytic hierarchy process (AHP). The SWOT analysis is a useful tool for creating future strategies but also has some weaknesses in practice. SWOT is the overall evaluation of a company’s strengths, weaknesses, opportunities, and threats. Even it has some deficiencies, The SWOT analysis is no doubt a valuable tool in the field of business strategy because it invites decision-makers to consider important aspects of their organization’s environment and helps them organize their thoughts (Wang, 2007). Today, the Analytic Hierarchy Process (AHP) of Saaty (1980) is one of the most popular and powerful methods for decision making. AHP is generally used to derive priorities based on sets of pairwise comparisons (Forman and Peniwati, 1998). The AHP approach is a multi-criteria decision-making method that uses hierarchic or network structures to represent a decision problem and then develops priorities for the alternatives based on the decision maker’s judgments throughout the system. It addresses the issues of how to structure a complex decision problem, identify its criteria (tangible or intangible), measure the interaction among them and finally synthesize all the information to arrive at priorities, which depict preferences (Dyer, 1990; Saaty, 1986, 1987, 1990).  For this purpose, first of all: the strengths and weaknesses of the forest products industry and their opportunities and threats originating from the sector and district were determined using the SWOT matrix. Afterwards the information obtained from the SWOT matrix were integrated into the AHP hierarchy and the optimum strategy was tried to find out. The used data were gotten from the industry database of Union of Chambers and Commodity Exchanges of Turkey (TOBB).
Keywords: 15. Life on land